Tracking Formation of a Lava Lake From Ground and Space: Masaya Volcano (Nicaragua), 2014–2017. (27th February 2018) - Aiuppa, Alessandro; de Moor, J. Maarten; Arellano, Santiago; Coppola, Diego; Francofonte, Vincenzo; Galle, Bo; Giudice, Gaetano; Liuzzo, Marco; Mendoza, Elvis; Saballos, Armando; Tamburello, Giancarlo; Battaglia, Angelo; et al.
Abstract: A vigorously degassing lava lake appeared inside the Santiago pit crater of Masaya volcano (Nicaragua) in December 2015, after years of degassing with no (or minor) incandescence. Here we present an unprecedented‐long (3 years) and continuous volcanic gas record that instrumentally characterizes the (re)activation of the lava lake. Our results show that, before appearance of the lake, the volcanic gas plume composition became unusually CO2 rich, as testified by high CO2 /SO2 ratios (mean: 12.2 ± 6.3) and low H2 O/CO2 ratios (mean: 2.3 ± 1.3). The volcanic CO2 flux also peaked in November 2015 (mean: 81.3 ± 40.6 kg/s; maximum: 247 kg/s). Using results of magma degassing models and budgets, we interpret this elevated CO2 degassing as sourced by degassing of a volatile‐rich fast‐overturning (3.6–5.2 m 3  s −1 ) magma, supplying CO2 ‐rich gas bubbles from minimum equivalent depths of 0.36–1.4 km. We propose this elevated gas bubble supply destabilized the shallow (<1 km) Masaya magma reservoir, leading to upward migration of vesicular (buoyant) resident magma, and ultimately to (re)formation of the lava lake. At onset of lava lake activity on 11 December 2015 (constrained by satellite‐based MODIS thermal observations), the gas emissions transitioned to more SO2 ‐rich composition, and the SO2 flux increased by a factor ∼40% (11.4 ± 5.2 kg/s) relative to background degassing (8.0 kg/s), confirming faster than normal (4.4 versus ∼3 m 3  s −1 ) shallow magma convection. Based on thermal energy records, we estimate that only ∼0.8 of the 4.4 m 3  s −1 of magma actually reached the surface to manifest into a convecting lava lake, suggesting inefficient transport of magma in the near‐surface plumbing system. Key Points: We present a multidisciplinary study of the formation mechanisms of a lava lake at Masaya (Nicaragua), December 2015 We find evidence for a gas CO2 /SO2 ratio precursor prior to (re)formation of the Masaya lava lake We interpret formation of the lava lake as driven by elevated supply of deeply sourced CO2 ‐rich gas bubbles